Stakeholders of Web Applications Requirements - Oliveros, Alejandro (2015)
Stakeholders play an important role to establish the requirements of a software system. In fact, systems are built to meet the needs of some stakeholders. They are also source of key requirements; not reaching to all the stakeholders of a system jeopardizes its completeness since the requirements are not detected. In Requirement Engineering, the matter has not been dealt with the required depth and consistency, thus the notion of “stakeholders” remained ambiguous as well as their associated processes. Especially, there is a lack of clear concepts regarding their role in Web applications, a subject that seems controversial (as confirmed by literature). We made ourselves the following question: who are the web application stakeholders and how should we manage them? Our special interest focuses on the local web applicationsdevelopment organizations. For this, we have conducted some field research that covered not only the stakeholder-related aspects, but also other areas of the requirement processes. This field research is a first approach to the problem and provides some answers, but also raises questions and suggests possible answers to some others.